Transplantasi Victim Impact Statement Dalam KUHAP Baru: Perbandingan Kanada, Belanda Dan Australia - Noviantama, Doni; Wafi, Muhammad Syafiq; Putri, Salsabella Sania; Martha, Aroma Elmina (Universitas Islam Indonesia, 2026)
The Indonesian criminal justice system inevitably situates the victims in a passive position, they are merely able to witness the law enforcement process without having an independent space to express their experiences. Meanwhile, in other countries such as Canada, the Netherlands, and Australia, the victims are directly involved in the law enforcement process by being given the opportunity to submit a Victim Impact Statement (VIS) at a conference. Therefore, the researcher focused on two primary issues: how is the VIS regulated in the Canadian, the Dutch, and the Australian legal systems? And how is the VIS transplant model in the New Criminal Procedure Code, starting from its form, content, parties who submit it, and crimes for which victims may submit a VIS? The research method used is normative legal research using primary and secondary legal materials. The results of the study indicate that Canada, the Netherlands, and Australia have comprehensively regulated VIS in their legal systems as a form of strengthening victim participation in the criminal justice system. The VIS regulations in Canada, the Netherlands, and Australia can be used as a basis for a comprehensive transplantation of VIS law in the New Criminal Procedure Code, starting from the form of VIS to the crimes for which victims can submit a VIS. Moreover, the philosophical basis for VIS aligns with existing Indonesian values, allowing legislators to transplant VIS into formal law. Therefore, researchers recommend transplanting VIS provisions into the New Criminal Procedure Code (KUHAP), which specifically regulates the form and content of VIS, the parties who can file a VIS, the crimes for which victims can file a VIS, and the VIS filing procedure.